2013
DOI: 10.1016/j.neuropharm.2013.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal P/Q- and R-type calcium channel blockade of spinal substance P release and c-Fos expression

Abstract: Intrathecal (IT) studies have shown that several voltage sensitive calcium channels (VSCCs), such as the L-, N- and T-type may play roles in nociception and that of these only the N-type regulates primary afferent substance P (SP) release. However, the actions of other VSCCs at the spinal level are not well known. We investigated the roles of spinal P/Q- and R-type VSCCs, by IT administration of R-type (SNX-482) and P/Q-type (ω-agatoxin IVA) VSCC blockers on intraplantar formalin-evoked flinching, SP release f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 50 publications
(83 reference statements)
1
16
0
Order By: Relevance
“…Additionally, central blockade of CaV2.2 is effective in treatment of cases of chronic pain that are intractable to other interventions [11]. Other subtypes of calcium channels, such as CaV2.3 (R-type) [54; 72; 81] or CaV3 (T-type)[35; 51; 58], have also been indicated to play important roles in chronic pain. The CaV2.3-selective blocker, SNX-482, has been reported to block the C- and Aδ- fiber neurotransmission in animal models of chronic neuropathic pain [54] and reduce formalin induced paw-flinching and FOS-expression in the ipsilateral spinal cord [81].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, central blockade of CaV2.2 is effective in treatment of cases of chronic pain that are intractable to other interventions [11]. Other subtypes of calcium channels, such as CaV2.3 (R-type) [54; 72; 81] or CaV3 (T-type)[35; 51; 58], have also been indicated to play important roles in chronic pain. The CaV2.3-selective blocker, SNX-482, has been reported to block the C- and Aδ- fiber neurotransmission in animal models of chronic neuropathic pain [54] and reduce formalin induced paw-flinching and FOS-expression in the ipsilateral spinal cord [81].…”
Section: Discussionmentioning
confidence: 99%
“…In present study, we did not analyze the pain behavior after SP injection, and there was no behavioral change or extraordinary reaction after injection compared with the control group. However, many studies suggested that SP of the spinal cord is linked closely to nociceptive change [40][41][42]; so, a welldesigned study is needed to clarify the pain behavior after SP injection.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic research approaches confirmed this, with Ca v 2.3 knockout mice exhibiting reduced pain perception (Saegusa et al, 2000;Yang and Stephens, 2009). In pharmacological studies, intrathecal delivery of the Ca v 2.3 channel blocker SNX-482, a toxin from the tarantula Hysterocrates gigas, produces analgesia in animal models of neuropathic pain Terashima et al, 2013). Despite the clear functional importance of Ca v 2.3 channels in pain pathways, the mechanisms by which they are modulated by GPCRs have not yet been adequately examined (Rittenhouse, 2014).…”
Section: Introductionmentioning
confidence: 99%